Market reactions to the announcement of sukuk: evidence from Malaysian market / Muzrifah Mohamed Mohamed - Mohamed, Muzrifah Mohamed (2014)
The lack of considerable effort in understanding the investor’s ability to perform strategy from market reactions trend and how the market behaves towards this Islamic debt issuance and stock price adjustment is becoming a growing concern. Hence, this research is aimed to examine whether announcements of sukuk issuance carry any new information to give impact on market reactions from period of 2001 until 2013 in Malaysian market. Consideration is given to investigate the impact of this Islamic debt on stock’s return surrounding the 2007-2008 financial crisis. It specifically studies market reaction using Malaysian listed firms as a setting. This research is based on data obtained from Bursa, Bloomberg and Datastream. Using standards event study methodology of Brown and Warner (1985), the data was analyzed to determine the issuer’s stock return over a certain event windows. The research shows positive sign in Malaysian sukuk market that probably reason of investor’s awareness to switch to more secure and Shariah compliance securities after financial crisis and this provide signal to investor strategies to hold the stock until 61-day in order to earn an abnormal return. The results also revealed that large firms exhibit reversal behaviour with significantly outperformed small firms at 61-day of event window. The significant findings in this study contribute clearer evidence and strategies concerning returns and price adjustment, may encourage more investors to invest in Islamic debt in the future and for would-be investors and issuers. This study provides some recommendations, one of them is future research could be tested on the impact of capital structure beyond Malaysian market and compared between two or more markets perhaps between advanced and emerging economies.